A Wilder Rose [large type] - Albert, Susan Wittig (Thorndike Press large print core series., 2014)
Laura Ingalls Wilder is widely loved as the author of the Little House books that detail her life growing up in woods and on the prairies that were the frontiers of her time. Yet unknown to readers and publishers of the time and even until recently, Laura's daughter Rose had a substantial hand in crafting those stories for children. Rose was a well-recognized writer on her own, and it was she who encouraged her mother to write, then substantially cleaned up her stories so they were fit for publication. In A Wilder Rose: Rose Wilder Lane, Laura Ingalls Wilder, and Their Little Houses, author Susan Wittig Albert fictionalizes this real-life story while shedding light on the lives of both Laura and her daughter.